Application of Express Methods for the Detection of Explosive Substances - Askerov, K.A.; Ahmadova, S.T. (Herald of Azerbaijan Engineering Academy, 2023)
The article studies the main types of explosives, identification tools, and theoretical knowledge about the main properties and parts of explosives. Also, the application characteristics of express methods for detecting explosive substances are defined. It is shown that a new format approach and modern new technologies are one of the most important directions in the determination of explosives. Adaptation of the technical means used in the detection of explosives to international standards is investigated. The devices used to identify explosives and their characteristics are analyzed.